IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS DESKRIPSI PADA SISWA KELAS X SMA NEGERI 18 BONE - Elis; Andi Srimularahmah; Muhammad Asdar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the implementation of the Make a Match cooperative learning model in improving the descriptive text writing skills of tenth-grade students at SMA Negeri 18 Bone. The research employed Classroom Action Research (CAR), which was conducted in two cycles consisting of the stages of planning, implementation, observation, and reflection. The subjects of the study were 31 students. Data were collected through observation and writing tests, while the data were analyzed using quantitative and qualitative descriptive techniques.The results showed a significant improvement in students’ descriptive text writing skills. In the pre-cycle stage, the average score was 71.8 with a mastery level of 38.71%. In Cycle I, the average score increased to 76.8 with a mastery level of 64.52%, and in Cycle II, it further increased to 80.9 with a mastery level of 87.10%. Improvements were also observed in the aspects of content, text structure, diction, and language use. In addition, students’ learning activities and motivation improved, as indicated by greater participation, cooperation, and engagement in the learning process. Therefore, it can be concluded that the implementation of the Make a Match cooperative learning model is effective in improving students’ descriptive text writing skills and in creating an active, collaborative, and enjoyable learning environment.